2021
DOI: 10.1103/physrevb.103.184202
|View full text |Cite
|
Sign up to set email alerts
|

Subdiffusion in a one-dimensional Anderson insulator with random dephasing: Finite-size scaling, Griffiths effects, and possible implications for many-body localization

Abstract: We study transport in the boundary-driven XX spin chain with onsite disorder and randomly positioned onsite dephasing, observing a transition from diffusive to subdiffusive spin transport below a critical density of sites with dephasing. We then present an exactly solvable semiclassical model of conductors and insulators, which exhibits both diffusive and subdiffusive phases, and qualitatively reproduces the results of the quantum system. The subdiffusion in these models is a consequence of rare insulating reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…( 11) is polynomial in resources, the stationary solution is obtained exactly by solving ∂ t C = 0. This is given by [20,21]…”
Section: Observables a Equal-time Correlation Function And Currentmentioning
confidence: 99%
“…( 11) is polynomial in resources, the stationary solution is obtained exactly by solving ∂ t C = 0. This is given by [20,21]…”
Section: Observables a Equal-time Correlation Function And Currentmentioning
confidence: 99%
“…The exponent θ 0 in (56) vanishes as |ξ| → ∞ in the RM. The strongest low-frequency divergence [S(ω)] is however not ∼ 1/ω (indeed, as noted in [2] such a strong divergence would violate an elementary sum rule) because the exponential term in ( 53) modifies the exponent.…”
Section: Floquet Systemsmentioning
confidence: 97%
“…1a. The exponent θ characterising the low-frequency divergence of [S(ω)] in region II jumps at the transition (56).…”
Section: Floquet Resonance Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to quantify the density fluctuations of the clean boson, we average the absolute value of the deviation of its density from the mean value, stood as resulting from an Anderson insulator globally coupled to a weak, non-Markovian, local noise. While it is known [44][45][46][47][48] that Anderson localization is unstable with respect to global noise, a recent work [49] has demonstrated that coupling of an Anderson insulator to a local Markovian white noise leads to a logarithmically slow particle transport and entanglement growth. Our dynamics differs from that of Ref.…”
Section: A Time-dependent Hartree Approximationmentioning
confidence: 99%